The Effect of Digital Technology on the Development of Halal Tourism in Southeast Asia - Akim Akim; Neneng Konety; Viani Puspita Sari; Nurfarah Nidatya (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Tourism is experiencing very rapid development. The tourism that is now very popular with the world community is halal tourism which is starting to be in great demand for halal tourism by world Muslim tourists. Along with the entry of the era of technological digitalization in this millennial era, many tourism industries use digital media as a means of promotion. The presence of digital media influences the behavior of tourists and the public. This research intends to see how the influence of digitalization of technology on the development of halal tourism in Southeast Asia. Qualitative data analysis methods are used in this study so that it can produce descriptive data in the form of writing. Data is analyzed by content analysis and content description. Content analysis is a way to learn and understand the meaning of sources that correlate with assessment. The results of this study show that the existence of digital media information on tourism has a positive impact on the development of halal tourism in Southeast Asia. With the existence of digital technology platforms, it can promote tourist destinations to everyone easily and at a low cost. However, the impact of digitalization media also has a negative influence, namely misuse of applications and misinformation that affects the development of halal tourism through digital technology.